URINARY HIPPURIC ACID LEVEL AS A BIOLOGICAL INDICATOR OF TOLUENE EXPOSURE ON BATIK WORKERS (CASE STUDY: HOME- SCALE BATIK INDUSTRY AT KULON PROGO, YOGYAKARTA) - Artsani Hanif Anka, Annisa
Urinary hippuric acid is one of the biomonitoring parameters of toxic organic exposure such as toluene. Based on preliminary research, toluene was found in the working area of the batik industry in Yogyakarta, Indonesia. Repeated exposure to a low concentration of toluene may lead to chronic effects such as central nervous system damage. Urinary hippuric acid (uHA) level was evaluated and correlated with toluene exposure indications. The sample was collected once at the end of the shift, then urinary creatinine and hippuric acid were measured using UV-Vis Spectrophotometer. Toluene in inhaled air collected using personal sampler pump and measured using Gas Chromatography-Mass Spectroscopy (GCMS). The result showed that workers with toluene exposure symptoms have a higher concentration of uHA than workers who are not experiencing any symptoms. Logistic regression analysis gives an Odds Ratio (OR) on workers with a work period of more than 2 years, writing workers, and stamping workers 6.43, 6.75, and 9.00, respectively. Organic aliphatic, alicyclic, and aromatic hydrocarbon were found in inhaled air sample and there was a compound that suggested as a toluene atmospheric degradation product. Other than that, workers who have urinary creatinine concentration outside the normal range area are a higher percentage than in the control group (47% and 17% respectively). Based on toluene indicator variables, it showed that batik worker has a higher probability and indication on having a toluene exposure. Even though uHA concentration of all workers is still below the recommended value (BEI), risk factors that affecting the elevation of uHA level should be considered and managed to reduce the risk of having a chronic effect on the workers.